2010
DOI: 10.1111/j.1747-4477.2009.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Substance P and CGRP expression in dental pulps with irreversible pulpitis

Abstract: The purpose of this study was to compare substance P (SP) and calcitonin gene-related peptide (CGRP) expression in pulp tissue with clinically diagnosed symptomatic and asymptomatic irreversible pulpitis. Healthy pulps acted as controls. Five normal pulps and 40 with irreversible pulpitis (20 symptomatic and 20 asymptomatic) were obtained from 45 different patients. SP and CGRP expression was determined by competition binding assays using enzyme immunoassay. anova and Mann-Whitney tests were used to ascertain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…[192021] While it has been shown that local anesthetic ingredients can affect the result of such studies by slowing the release of neuropeptides from dental pulp as well as lowering SP concentration in pulp tissue and diluting it. [2223] Some of these studies were performed on samples of coronal pulp tissue taken after local anesthesia administration.…”
Section: Discussionmentioning
confidence: 99%
“…[192021] While it has been shown that local anesthetic ingredients can affect the result of such studies by slowing the release of neuropeptides from dental pulp as well as lowering SP concentration in pulp tissue and diluting it. [2223] Some of these studies were performed on samples of coronal pulp tissue taken after local anesthesia administration.…”
Section: Discussionmentioning
confidence: 99%
“…Sattari et al . concluded that ‘the expression of CGRP and substance P is significantly higher in pulps with irreversible pulpitis compared with healthy pulps (1).’ I have some comments on this work. At first, the work is based on few subjects without good case‐control matching; hence, it is limited, further generalized due to main statistical weakness.…”
mentioning
confidence: 87%
“…Patients had moderate-to-severe spontaneous pain of approximately 24-h duration, and they had not taken any anti-inflammatory medications, had either a normal or a hypersensitive reaction to percussion, and had no radiographic evidence of periradicular pathosis. 1,11,12 Pulp sensitivity tests…”
Section: Study Groupsmentioning
confidence: 99%
“…2 It is primarily localized at the C and A-δ sensory fibers, which display wide innervation throughout the body, but C-type fibers are closely associated with pulp microcirculation. 1,20 Several studies have reported an increased expression of CGRP on teeth with irreversible pulpitis compared with teeth having healthy pulps. 1,3,11,12,21 In this study, we observed higher values of the gene, of the gene of the receptor, and of the expression of CGRP in the irreversible pulpitis group (P = .0001).…”
Section: Expression Of Cgrp In Teeth With Irreversible Pulpsmentioning
confidence: 99%
See 1 more Smart Citation